2022
DOI: 10.1016/j.tranpol.2022.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Mask-wearing intentions on airplanes during COVID-19 – Application of theory of planned behavior model

Abstract: The COVID-19 pandemic has devastated the air transport industry, forcing airlines to take measures to ensure the safety of passengers and crewmembers. Among the many protective measures, mask mandate onboard the airplane is an important one, but travelers' mask-wearing intentions during flight remain uninvestigated especially in the US where mask use is a topic of on-going debate. This study focused on the mask use of airline passengers when they fly during COVID-19, using the theory of planned behavior (TPB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 81 publications
(127 reference statements)
1
24
0
Order By: Relevance
“…This is aligned with the theory and with the results of recent studies involving the COVID-19 pandemic (Barile et al, 2021;Gaube, Fischer, & Lermer, 2021;Trifiletti, Shamloo, Faccini, & Zaka, 2021;Wollast, Schmitz, Bigot, & Luminet, 2021). Despite at least one divergent result in a recent study (Pan & Liu, 2022), a meta-analysis covering 83 papers about TPB and COVID-19 confirmed subjective norms as a significant predictor of both behavioral intention and behavior (Fischer & Karl, 2022). Subjective norms are influenced by normative beliefs considering the expectations of relatives, friends, and peers (Ajzen & Madden, 1986).…”
Section: Discussionsupporting
confidence: 81%
“…This is aligned with the theory and with the results of recent studies involving the COVID-19 pandemic (Barile et al, 2021;Gaube, Fischer, & Lermer, 2021;Trifiletti, Shamloo, Faccini, & Zaka, 2021;Wollast, Schmitz, Bigot, & Luminet, 2021). Despite at least one divergent result in a recent study (Pan & Liu, 2022), a meta-analysis covering 83 papers about TPB and COVID-19 confirmed subjective norms as a significant predictor of both behavioral intention and behavior (Fischer & Karl, 2022). Subjective norms are influenced by normative beliefs considering the expectations of relatives, friends, and peers (Ajzen & Madden, 1986).…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have validated the utility of RAA/TPB to understand intentions to wear a mask in public and to get vaccinated. Pan and Liu (2022) found that attitude and descriptive norm predicted intention to use a mask on an airplane during COVID-19, with attitude being the primary driver for young and middle-aged travelers. Andarge and colleagues (2020) found subjective norm (called injunctive norm in RAA) and perceived behavioral control to be the belief factors that should be targeted for interventions to help adults with chronic conditions practice personal prevention measures.…”
Section: Implications For Occupational Health Practicementioning
confidence: 95%
“…In addition to the direct impact of the three components of the TPB, Frounfelker et al [ 13 ] and Li et al [ 14 ] also found mediating roles of the three constructs in interpreting individuals’ preventive intentions or behaviors against COVID-19. In contrast to the above studies, Pan and Liu [ 15 ] and Ahmad et al [ 16 ] uncovered insignificant effects of perceived behavioral control on individuals’ intentions to accept COVID-19 epidemic prevention measures. Patwary et al’s [ 17 ] research showed no significant effects of attitude or subjective norms on people’s intention to be vaccinated against COVID-19.…”
Section: Introductionmentioning
confidence: 90%